Effect of pyrolysis on elastic properties and microstructure of organic-rich Mancos shale - Pervukhina, M.; Uvarova, Y.; Dautriat, J.; Dewhurst, D.; Patrusheva, N.; Lebedev, Maxim (SEG, 2014)
We have studied changes of static and dynamic elastic properties of the organic-rich Mancos shale caused by heating to the temperature within the range 380°C-550°C. An increase of ultrasonic velocities and static Young's moduli has been observed in the samples that experienced temperatures up to ~400°C. Further heating to temperatures up to 550°C has led to the decrease of elastic moduli. The samples subjected to temperatures above 430°C show an increase in stress sensitivity, which implies microcrack generation. Micro-CT images of small samples have been obtained to inspect the microstructural changes caused by this dry pyrolysis. Comparison of the registered micro-CT images of Mancos shale samples subjected to temperatures up to 470°C shows significant shrinkage of the kerogen that fills pore spaces resulted from bitumen expulsion into the pores.